2013
DOI: 10.1016/j.biortech.2013.06.125
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of biofouling on the photobioreactors of the Offshore Membrane Enclosures for Growing Algae (OMEGA) system

Abstract: The influence of PBR composition [clear polyurethane (PolyU) vs. clear linear low-density polyethylene (LLDPE) (top) and black opaque high-density polyethylene (bottom)] and shape (rectangular vs. tubular) on biofouling and the influence of biofouling on algae productivity were investigated. In 9-week experiments, PBR biofouling was dominated by pennate diatoms and clear plastics developed macroalgae. LLDPE exhibited lower photosynthetic-active-radiation (PAR) light transmittance than PolyU before biofouling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 27 publications
0
28
0
Order By: Relevance
“…A major group of inhabitants in the initial biofilm formed under conditions where light is present, phototrophic biofilms, are cyanobacteria and microalgae [12,14]. There are many practical issues arising from phototrophic biofilm formation, including problems with biofouling on technical surfaces such as ship hulls and lowered light transmittance in photobioreactors [7,14]. Recent research shows that bacteria, both phototrophs and chemotrophs, can use the quality of the light available to make important lifestyle decisions such as persistence in a single cell state or as a surface-attached biofilm [5].…”
Section: Introductionmentioning
confidence: 99%
“…A major group of inhabitants in the initial biofilm formed under conditions where light is present, phototrophic biofilms, are cyanobacteria and microalgae [12,14]. There are many practical issues arising from phototrophic biofilm formation, including problems with biofouling on technical surfaces such as ship hulls and lowered light transmittance in photobioreactors [7,14]. Recent research shows that bacteria, both phototrophs and chemotrophs, can use the quality of the light available to make important lifestyle decisions such as persistence in a single cell state or as a surface-attached biofilm [5].…”
Section: Introductionmentioning
confidence: 99%
“…Gulls and coots are omnivores that are known to be well adapted to urbanized environments [44,45] which may explain their opportunistic foraging behavior on the biofouling that developed on the PBRs. The PBR biofouling community in Moss Landing harbor was characterized [46] and found to included diatom films, seaweeds, crustaceans, and bryozoans—known food resources for gulls and coots [28,44]. The observed spikes in the number of coots associated with PBRs may be related to their behavioral tendency to aggregate during foraging [47].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the submerged surfaces of OMEGA PBRs provide substrate, refugia, and habitat for sessile and associated organisms [46], thereby increasing local productivity and diversity and potentially improving coastal water quality [20,21,56]. …”
Section: Discussionmentioning
confidence: 99%
“…Interest in algae is also driven by perceived high productivities and the potential for carbon uptake and sequestration in mitigating carbon dioxide emissions from power plants. Sea-based floating membrane bioreactors have also been proposed to enable large-scale off-shore farming of algal biomass using municipal wastewaters as nutrient sources (Howell, 2009;Harris et al, 2013). Commercial yields are unlikely to exceed approximately 80 metric tons dry matter per hectare per year (Scott et al, 2010) although more optimistic estimates are frequently made.…”
Section: Industrial and Energy Cropsmentioning
confidence: 99%